A Busca pela ascensão feminina no PDS Virola Jatobá, Anapu-PA - CASTRO, Roberta Rowsy Amorim de (Universidade Federal do Pará, 2018)
This research aimed to analyze the role of women in Virola Jatobá PDS, Anapu-Pará, its importance and representation in productive, economic and social activities and describe how you are giving the search for female ascent through the association. They interviewed 18 women farmers and it was found that these participate in the work processes in farming systems, creations and extraction. With regard to the accompanying activities and extra income, all interviewees contribute to the monthly income of their families. Women PDS exert important collective role, to organize themselves into associations and other gender, highlighting the search for insertion in various scenarios. This action contributes to recognize themselves as workers and not just as helpers.